Cobalt-Catalyzed Regioselective Hydroformylation of Allylic Alcohol Esters - Du, Zhenhao; Lu, Wenxin; Chong, Qinglei; Meng, Fanke (Synthesis, 2025)
Aliphatic aldehydes are important building blocks in organic synthesis due to their high reactivity and versatility. Herein, we report a simple, mild and efficient method for the hydroformylation of allyl alcohol esters under cobalt catalysis. This procedure offers good functional group tolerance, moderate to good product yields and exclusive chemo- and regioselectivity, making it an attractive method to prepare aldehydes with linear selectivity.
Keywords: hydroformylation; synthesis gas; cobalt; functionalized olefins; allyl alcohol derivatives